A VISUAL NARRATIVE: JAVANESE MASK COLLECTIONS AT THE MPU TANTULAR MUSEUM Identification of the East Java Cultural Diversity Mask Collection: A VISUAL NARRATIVE: JAVANESE MASK COLLECTIONS AT THE MPU TANTULAR MUSEUM Identification of the East Java Cultural Diversity Mask Collection - Wahyuningtyas, Tri; Hidajat, Robby (International Journal of Performing Arts (IJPA), 2025)
This article aims to identify and classify the mask collections at the Mpu Tantular StateMuseum, Sidoarjo, as a visual narrative of the cultural richness of East Java and itssurrounding regions. Through in-depth identification activities conducted from September17–19, 2025, the mask collections were classified into three main variants based on regions:Topeng Malang (Malang Masks), Topeng Madura (Madura Masks), and some other regionalmasks.The Malang mask collection, the most numerous collection, represents the epic tale ofPanji Asmorobangun. Its characteristic features include symmetrical, refined carvings andthe use of philosophical colors. The green color shown by Panji symbolizes chivalry andtranquility, contrasting sharply with the fiery red possessed by Klana Sewandana, whichrepresents anger. The faded colors on the ancient masks emphasize their inherent historicaland spiritual gravitas and value as evidence of the preservation of this noble art form.The Madura mask collection, associated with the Madura’s puppet maskperformances, displays characters that reflect the resilience of the community from theMadura island, also known as the salt island. Their characteristics are simpler but firm, hard,and expressive (such as bulging eyes or fangs), implying a strong fighting spirit andstraightforward demeanor.The other regional masks group completes the Nusantara (an archipelago country)mosaic, including collections from Cirebon (such as the White Elephant mask), Yogyakarta,as well as the Sandur mask (from Jombang/ Tuban) and the Dongkrek mask (from Madiun).The presence of these masks from outside the immediate region confirms East Java’s culturalconnection and acculturation with the wider archipelago.Overall, the mask collection at the Mpu Tantular museum functions as a "spiritualwindow" that reflects the contrast and unity of values, ranging from the agrarian idealism(Malang) to the coastal fighting spirit (Madura). These artifacts are an invaluable treasurethat ensures moral philosophy and local wisdom continue to live on as an educationalmedium for future generations.